The Situation of Parents in the Curricular Commonplaces: A Place of Equal Rank? - Pushor, Debbie (LEARNing Landscapes, 2009)
Schwab (1973) argued that four commonplaces of equal rank must be taken into account in curriculum making: students, teachers, subject matter and milieus. While he insisted that none of the commonplaces can be omitted without a vital loss, attention to milieus, particularly in relation to parents and families (rather than schools or classrooms), is largely being omitted in teacher education curriculum. This article explores how a teacher education curriculum attending to the positioning of parents helped interrupt one teacher’s story of parents. The article challenges us to consider who is rendered in/visible, who is in/validated, who finds schooling an educative process—and who is/does not—in the dominant plotline of parents as outsiders to curriculum.